Glucagon-like peptide-2 modulates neurally evoked mucosal chloride secretion in guinea pig small intestine in vitro - Baldassano, Sara (American Physiological Society, 2009)
Glucagon-like peptide-2 (GLP-2) is an important neuroendocrine peptide in intestinal physiology. It influences digestion, absorption, epithelial growth, motility, and blood flow. We studied involvement of GLP-2 in intestinal mucosal secretory behavior. Submucosal-mucosal preparations from guinea pig ileum were mounted in Ussing chambers for measurement of short-circuit current (I(sc)) as a surrogate for chloride secretion. GLP-2 action on neuronal release of acetylcholine was determined with ELISA. Enteric neuronal expression of the GLP-2 receptor (GLP-2R) was studied with immunohistochemical methods. Application of GLP-2 (0.1–100 nM) to the serosal or mucosal side of the preparations evoked no change in baseline I(sc) and did not alter transepithelial ionic conductance. Transmural electrical field stimulation (EFS) evoked characteristic biphasic increases in I(sc), with an initially rapid rising phase followed by a sustained phase. Application of GLP-2 reduced the EFS-evoked biphasic responses in a concentration-dependent manner. The GLP-2R antagonist GLP-2-(3-33) significantly reversed suppression of the EFS-evoked responses by GLP-2. Tetrodotoxin, scopolamine, and hexamethonium, but not vasoactive intestinal peptide type 1 receptor (VPAC1) antagonist abolished or reduced to near zero the EFS-evoked responses. GLP-2 suppressed EFS-evoked acetylcholine release as measured by ELISA. Pretreatment with GLP-2-(3-33) offset this action of GLP-2. In the submucosal plexus, GLP-2R immunoreactivity (-IR) was expressed in choline acetyltransferase-IR neurons, somatostatin-IR neurons, neuropeptide Y-IR neurons, and vasoactive intestinal peptide-IR neurons. We conclude that submucosal neurons in the guinea pig ileum express GLP-2R. Activation of GLP-2R decreases neuronally evoked epithelial chloride secretion by suppressing acetylcholine release from secretomotor neurons.